2023
DOI: 10.1021/acs.jafc.2c07881
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Anti-Hyperuricemic Activity of Xanthine Oxidase Inhibitory Peptides from Pacific White Shrimp and Swimming Crab Based on Molecular Docking Screening

Abstract: The xanthine oxidase (XO) inhibitory peptides from pacific white shrimp or swimming crab were identified by molecular docking, and the anti-hyperuricemic activity of the peptides was confirmed in hyperuricemic cells. In our study, 17 novel XO inhibitory peptides were purified from pacific white shrimp or swimming crab, and Ala-Glu-Ala-Gln-Met-Trp-Arg (AEAQMWR, 891.01 Da, IC 50 = 8.85 ± 0.05 mM) exhibited the greatest XO inhibitory activity in vitro. Molecular docking results indicated that attractive charge, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In addition, 1 and 5 mg/mL TAP reduced HUA cell supernatant UA by 16.13 and 33.62% ( P < 0.01) in a concentration-dependent manner. Similarly, Mao et al found that after treatment with the peptides AEAQMWR, EFGMGGW, and AGGINLAR, the UA content of HK-2 cells decreased significantly.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, 1 and 5 mg/mL TAP reduced HUA cell supernatant UA by 16.13 and 33.62% ( P < 0.01) in a concentration-dependent manner. Similarly, Mao et al found that after treatment with the peptides AEAQMWR, EFGMGGW, and AGGINLAR, the UA content of HK-2 cells decreased significantly.…”
Section: Resultsmentioning
confidence: 83%
“…Small molecular weight (1 kDa) oligopeptides tend to exhibit bioactivity and are more easily absorbed by the body. 17 At present, the molecular weight of most identified XOD inhibitory peptides and/or antihyperuricemic peptides is below 1000 Da, such as Ala-Glu-Ala-Gln-Met-Trp-Arg, 25 Ala-Leu-Pro-Met, 26 Leu-Trp-Met, 26 Pro-Glu-Trp, 27 Ala-Leu-Ser-Gly-Ser-Trp, Gly-Gly-Tyr-Gly-Ile-Phe, Met-Ala-Ile-Gly-Leu-Trp, 5 Ala-Cys-Glu-Cys-Asp. 12 After alkaline protease hydrolysis, the T. albacares protein is cut into small peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Walnut protein hydrolysate (Li et al, 2018) with XO inhibition effects also showed significant anti-hyperuricemia activity after oral administration. Mao et al (2023) employed virtual screening and structure optimization techniques to identify seven XO inhibitory peptides from shrimp. Among these, YNITGW displayed the most potent XO inhibitory effects, with an IC50 value of 9.78 ± 0.13 mM.…”
Section: Mechanisms Of Action Of Anti-hyperuricemia Peptidesmentioning
confidence: 99%
“…Mao et al. (2023) employed virtual screening and structure optimization techniques to identify seven XO inhibitory peptides from shrimp. Among these, YNITGW displayed the most potent XO inhibitory effects, with an IC50 value of 9.78 ± 0.13 mM.…”
Section: Bioactivities and Mechanisms Of Food‐derived Functional Pept...mentioning
confidence: 99%
“…115 Taken together, these studies suggest that seafood-derived peptides could be a potential inhibitor of XOD, mainly because these substances are rich in proteins, which are degraded to produce peptides of different lengths. 14,106 Peptides from other animals and their products have also demonstrated XOD inhibitory activities. For instance, Pei et al 90 identified XOD inhibitory peptides from fermented feather broth for the first time.…”
Section: Food and Function Reviewmentioning
confidence: 99%